2022
DOI: 10.3389/fimmu.2022.925558
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling at COVID-19 Onset Shows Disease Severity and Sex-Specific Dysregulation

Abstract: Backgroundmetabolic changes through SARS-CoV-2 infection has been reported but not fully comprehended. This metabolic dysregulation affects multiple organs during COVID-19 and its early detection can be used as a prognosis marker of severity. Therefore, we aimed to characterize metabolic and cytokine profile at COVID-19 onset and its relationship with disease severity to identify metabolic profiles predicting disease progression.Material and Methodswe performed a retrospective cross-sectional study in 123 COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 78 publications
(119 reference statements)
1
11
0
2
Order By: Relevance
“…According to the results obtained, kynurenine, phenylalanine and acetylcarnitine have strong association with the severity of COVID-19 infection. This is consistent with the findings of increased levels of kynurenine and phenylalanine for COVID-19 patients 3,8,15,16 and their negative correlation with the severity of infection 7,10 . Increased kynurenine levels in COVID-19 are associated with increased tryptophan degradation due to overactivation of the immune response through increased levels of interferon-gamma (increased inflammatory response) and strong T-cell activation 1,15 ; kynurenine pathway metabolites were shown to be associated with tricarboxylic acid cycle intermediates, inflammatory response, and cell death 4 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…According to the results obtained, kynurenine, phenylalanine and acetylcarnitine have strong association with the severity of COVID-19 infection. This is consistent with the findings of increased levels of kynurenine and phenylalanine for COVID-19 patients 3,8,15,16 and their negative correlation with the severity of infection 7,10 . Increased kynurenine levels in COVID-19 are associated with increased tryptophan degradation due to overactivation of the immune response through increased levels of interferon-gamma (increased inflammatory response) and strong T-cell activation 1,15 ; kynurenine pathway metabolites were shown to be associated with tricarboxylic acid cycle intermediates, inflammatory response, and cell death 4 .…”
Section: Resultssupporting
confidence: 92%
“…Impaired synthesis and metabolism of arginine, threonine, ornithine, citrulline and alanine in COVID-19 patients, especially under hypoxic conditions, has been reported in many studies 9,11,16,19 . Decreased serum levels of glutamate, citrulline, ornithine, glutamine, urea, fumarate, ADMA and SDMA in COVID-19 patients were associated with liver dysfunction 14 .…”
Section: Discussionmentioning
confidence: 93%
“…Several studies identified that inflammation, metabolism, and lipoprotein content act in unison to overall inform the status of specific disease state such as mild, moderate, or severe in COVID-19 patients and thus can help us to predict and stratify the disease severity [2; 3; 21; 36; 46; 50; 51; 52; 53]. Our cytokines and chemokine profiling showed that acute COVID-19 samples had a trend of highest levels of cytokines & chemokines compared with either HC, LTCS or Recov (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Many scientific reports identified the important role of metabolites in the blood serum and plasma of mild, moderate, severe, and recovered COVID-19 patients. In fact, in COVID-19 disease or any other viral infection, immune cells require a lot of energy to fight off the infection, therefore, their metabolic demands drastically increase to produce cytokines and chemokines [2; 3]. A previous study described that peripheral blood mononuclear cells (PBMCs) have a dysregulated glycolysis and oxidative phosphorylation related metabolic profile, with specifically higher lactate and lower glucose levels in mild and moderate COVID-19 patients compared either with healthy controls (HC), convalescent (Co) COVID-19 individuals [4].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in COVID-19 disease or any other viral infection, immune cells require a lot of energy to fight off the infection. Therefore, their metabolism demands a drastic increase to produce cytokines and chemokines ( 2 , 3 ). A previous study described that peripheral blood mononuclear cells (PBMCs) show a dysregulated glycolysis and oxidative phosphorylation related metabolic profile, with specifically higher lactate and lower glucose levels in mild and moderate COVID-19 patients compared with either healthy controls (HC) or convalescent (Co) COVID-19 individuals ( 4 ).…”
Section: Introductionmentioning
confidence: 99%